2022
DOI: 10.1021/acsami.2c15812
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Separator Modification with an N-Rich Conjugated Microporous Polymer for the Effective Suppression of Polysulfide Shuttle and Li Dendrite Growth

Abstract: Lithium−sulfur (Li−S) batteries are very promising high-energy-density electrochemical energy storage devices, but suffer from serious Li polysulfide (LiPS) shuttle and uncontrollable Li dendrite growth. Here, we show in situ polyolefin separator modification with an N-rich conjugated microporous polymer (NCMP) for advanced Li−S battery. In situ polymerization generates an ultrathin NCMP coating on the whole external surface and the internal surface of the separator, which is substantially different from the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Meanwhile, the Li + ion diffusion coefficient was calculated according to the Randles-Sevcik equation, which can reect the LiPS diffusion in electrolyte to some extent. 50,51 Obviously, the Li//S battery with the Cu/W 18 O 49 @PP separator exhibits the highest Li + ion diffusion coefficient compared to the other separators (Fig. 3g and h).…”
Section: Electrochemical Properties Of Li//s Batteriesmentioning
confidence: 95%
“…Meanwhile, the Li + ion diffusion coefficient was calculated according to the Randles-Sevcik equation, which can reect the LiPS diffusion in electrolyte to some extent. 50,51 Obviously, the Li//S battery with the Cu/W 18 O 49 @PP separator exhibits the highest Li + ion diffusion coefficient compared to the other separators (Fig. 3g and h).…”
Section: Electrochemical Properties Of Li//s Batteriesmentioning
confidence: 95%
“…Conjugated microporous polymers (CMPs) composed of light element as a new class of organic porous material, with a π-conjugated backbone, permanent nanopores, and robust stability, show great promise in Li–S batteries. Particularly, numerous polar units and structural designability make them an ideal molecular platform for binding LiPSs and catalyzing their conversion. For instance, Zhang et al reported an N-rich CMP-modified commercial polypropylene (PP) separator and confirmed that the CMP coating can inhibit LiPS shuttle by molecular sieving effect, Coulombic interactions and Li bond interactions . However, the CMP suffers from poor conductivity and other important functions such as LiPS catalytic conversion remain unexplored .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Zhang et al reported an N-rich CMP-modified commercial polypropylene (PP) separator and confirmed that the CMP coating can inhibit LiPS shuttle by molecular sieving effect, Coulombic interactions and Li bond interactions. 36 However, the CMP suffers from poor conductivity and other important functions such as LiPS catalytic conversion remain unexplored. 37 Recently, Chen et al developed a zwitterionic amorphous CMP with a nanotentacle structure on CNT.…”
Section: Introductionmentioning
confidence: 99%
“…Developing an advanced electrochemical energy storage system is of great significance for meeting the increasing demand for high energy density and environmentally friendly energy storage solutions. Lithium metal is a promising material due to its low electrochemical potential (−3.04 V) and high theoretical specific capacity (3860 mAh g –1 ). Lithium metal batteries (LMBs) have therefore become a focus, when paired with cathode materials such as oxygen, ,, sulfur, ,, and LiFePO 4 , their energy density can reach a new summit.…”
Section: Introductionmentioning
confidence: 99%
“…Lithium metal is a promising material due to its low electrochemical potential (−3.04 V) and high theoretical specific capacity (3860 mAh g −1 ). 1−4 Lithium metal batteries (LMBs) have therefore become a focus, when paired with cathode materials such as oxygen, 3,5,6 sulfur, 2,7,8 and LiFePO 4 , 9−11 their energy density can reach a new summit.…”
Section: Introductionmentioning
confidence: 99%